Botulism in waterfowl: case report in Argentina - María Florencia Ovelar; Germán José Cantón; Jorge Pablo García; María Belén Riccio; Alicia Raquel Rodríguez; María Isabel Farace; Ignacio Alvarez (Acta Veterinaria Scandinavica)
Abstract Introduction Botulism, a severe neuroparalytic disease caused by the botulinum toxin produced by Clostridium botulinum, poses significant threats to wild birds. This study describes a natural outbreak of type C botulism in waterfowl in the surroundings of a lagoon in Saavedra, Buenos Aires province, Argentina, during January 2021. The outbreak, affecting approximately 300 birds, was attributed to environmental conditions that allowed the proliferation of C. botulinum. Clinical signs included progressive weakness, paresis, flaccid paralysis, difficulties in locomotion and swimming, “limbing neck”, and nictitating membrane protrusion. No gross lesions were observed during autopsies, but mild congestion, hemorrhage, and pulmonary edema were noted microscopically. Toxin type C was detected in feces, serum samples, and lagoon water, confirming the diagnosis. This is the first documented report of waterfowl botulism in central Argentina and highlights the impact that delayed detection can have on bird populations. Background Botulism, a severe neuroparalytic disease caused by Clostridium botulinum neurotoxins, poses a significant risk to wild birds, especially waterfowl and their ecosystems. Recent trends show an increase in botulism outbreaks in wild birds, likely influenced by climate change impacting environmental factors. Unlike in humans, there is often a lack of regulation and surveillance of botulism in wild birds worldwide. Case presentation In January 2021, an outbreak of neurological disease characterized by locomotion difficulties, led to the deaths of approximately 300 waterfowl. Results confirmed BoNTs type C establishing the cause of the mortality. Conclusions This botulism outbreak underscores the critical need for early detection and intervention to prevent significant losses in wild bird populations.